Answer:
Step-by-step explanation:
To find the expression equivalent to the given equation, you must apply the exponent rule to raise a power to another power.
The given equation is:
(-3x^3y^2)(5x^5y^4)^2
To apply the exponent rule, you need to raise both the base (5x^5y^4) and the exponent (2) to the power of 2:
(-3x^3y^2)[(5x^5y^4)^2]
Now, use the exponent rule by multiplying the exponents:
(-3x^3y^2)(5^2x^(52)y^(42))
Simplify the exponents and the constant:
(-3x^3y^2)(25x^10y^8)
Now, multiply the constants and combine the like terms with the same variables:
-3 * 25 = -75
x^3 * x^10 = x^(3+10) = x^13
y^2 * y^8 = y^(2+8) = y^10
So, the equivalent expression is:
-75x^13y^10